Faecal concentrations of ceftiofur metabolites in finisher pigs administered intramuscularly with ceftiofur - Tara N. Gaire (Veterinary Medicine and Science, 2021)
Abstract The objective of this study was to determine the effects of dietary fibre level and source on faecal ceftiofur metabolites concentrations after intramuscular administration of therapeutic ceftiofur hydrochloride in finisher pigs. Pens of finisher pigs (n = 36), with an equal number of barrows and gilts, were randomly assigned to 1 of 3 dietary treatment groups: basal diet composed of corn grain and soy bean meal with no supplement and formulated to contain 8.7% neutral detergent fibre (NDF), supplemented with 20% distillers dried grains with solubles (a byproduct of the ethanol production from corn grain) formulated to contain 13.6% NDF, primarily insoluble fibre or supplemented with 14.5% sugar beet pulp formulated to contain 13.6% NDF. Faecal samples were collected 6–8 hr after ceftiofur injection from treated and untreated pen‐mate pigs on days 1 and 3 of the 3‐day treatment regimen. Faecal concentrations of ceftiofur metabolites, including the major metabolite, desfuroylceftiofur, were analysed by reverse‐phase high pressure liquid chromatography with ultraviolet detection. Overall, the faecal concentrations of ceftiofur metabolites did not differ significantly between the dietary treatments. The mean concentrations of metabolites tended to be lower (p = .1) on day 3 compared to day 1 of the 3‐day treatment regimen. Faecal concentrations of metabolites were not affected by the gender of the finisher pigs. The concentrations of ceftiofur metabolites in the faeces are likely reflective of the microbial activity in the hindgut. Our data suggest that the fibre level and source used in the study did not affect the faecal concentrations of ceftiofur metabolites.